YOUTH EMPOWERMENT: DIGITAL MARKETING AND CREATIVE DIGITAL PROCESSES TO IMPROVE BRANDING OF MSMEs AND HOMESTAY IN NAGARI MANINJAU - Yolanda Febriani Naserd; Hermansyah; Yuliana; Retnaningtyas Susanti; Adril Kudri; Rosy Witrin; Andre Saprilla; Ovili Agnesia; Hafiz Ikhsan; Randrianirina Leonel Juliano (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
This community service activity was carried out at Nagari Maninjau Tourism Village, West Sumatra. Nagari Maninjau Tourism Village has great potential in tourism. The objectives of this activity are: 1) Increasing youth knowledge in digital use, 2) Developing youth creativity in creating tourism content, especially MSMEs and homestays, 3) Having a positive impact on business actors to create a creative and innovative environment. The target of this activity is the youth of Nagari Maninjau who take part in training activities, especially the Maninjau Kreative group. The method of implementing this community service is carried out through 4 processes, namely: preparation, digital marketing training, creative digital process assistance, and assessment. Mentoring activities are carried out by direct visits and online via WhatsApp. Assessment is carried out to find out how the impact of activities that have been carried out by the community. The results of this activity are the increased knowledge of youth in digital marketing, then the implementation of homestay video content and culinary product design, to the formation of the Maninjau Kreatif group and Instagram Maninjau Kreatif Forum.